Too old to test? Prevalence and correlates of HIV testing among sexually active older adults. Issue 4 (19th May 2018) - Oraka, Emeka; Mason, Stacey; Xia, Mingjing
ABSTRACT: Older adults account for 17% of new HIV diagnoses in the US and are more likely to be diagnosed with HIV later in the course of the disease compared to younger people. We calculated the prevalence and associated factors of having ever been tested for HIV among sexually active older adults. We analyzed data from the 2008–2016 General Social Survey Limited to respondents ≥65 years of age who reported more than one sex partner(s) in past 12 months ( n = 757). HIV testing prevalence, prevalence ratios, and 95% confidence intervals were calculated by demographic variables and HIV-related risk behaviors. An estimated 16.3% of sexually active older adults have tested for HIV, and 15.9% were at increased risk for HIV infection (reported injection drug and/or crack–cocaine use, exchanging money for sex, more than three sex partners in the past year, or men who reported having sex with another man). In the adjusted model, adults aged 65–70, not married, self-identified as gay/bisexual, and at increased risk for HIV infection were more likely to have tested for HIV. An estimated 83.7% of sexually active older adults never tested for HIV. Strategies are needed to increase HIV awareness and testing among potentially high-risk older adults.